2020
DOI: 10.1245/s10434-019-08159-0
|View full text |Cite
|
Sign up to set email alerts
|

Workload Differentiates Breast Surgical Procedures: NSM Associated with Higher Workload Demand than SSM

Abstract: Background. Breast surgery has evolved with more focus on improving cosmetic outcomes, which requires increased operative time and technical complexity. Implications of these technical advances in surgery for the surgeon are unclear, but they may increase intraoperative demands, both mentally and physically. We prospectively evaluated mental and physical demand across breast surgery procedures, and compared surgeon ergonomic risk between nipple-sparing (NSM) and skin-sparing mastectomy (SSM) using subjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Surgeons experience greater physical symptoms such as neck and lower back pain, mental strain, and fatigue from performing open NSM compared to skin sparing mastectomy [ 6 , 29 ]. Thus, a more ergonomically sound technique with greater visualization is needed to improve surgeon working conditions and to improve the ease of the operation during open NSM.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons experience greater physical symptoms such as neck and lower back pain, mental strain, and fatigue from performing open NSM compared to skin sparing mastectomy [ 6 , 29 ]. Thus, a more ergonomically sound technique with greater visualization is needed to improve surgeon working conditions and to improve the ease of the operation during open NSM.…”
Section: Discussionmentioning
confidence: 99%
“…These tend to be more challenging to perform than conventional mastectomies, which likely account for the increased OR time. Indeed, Hallbeck et al 6 reported that among 172 procedures, skin-sparing and nipple-sparing mastectomies had longer operating times than other procedure types.…”
Section: Discussionmentioning
confidence: 99%
“…Nipple-sparing mastectomies (NSM) are an extremely demanding procedure for the surgeon. [1][2][3] The mental and physical workload for these surgeries is significant. As the nipple-sparing mastectomy procedure becomes more prevalent, 4 we cannot help but wonder the toll this will take on the surgeon.…”
Section: Pastmentioning
confidence: 99%